ON THE OCCURRENCE OF UPWELLING IN THE SOUTHERN MAKASSAR STRAIT - Ilahude, Abdul Gani (Marine Research in Indonesia, 1970)
The possibility of upwelling occuring off the coast of Sulawesi in the Southern Makassar Strait has been discussed by earlier workers (see e.g. Veen 1953, and Wyrtki 1961). Surface salinity data show higher values in June or July along the southwest coast of Sulawesi than the rest area to the west of it. The months June and July coincide with the southeast monsoon in the area. It is believed that the presence of such high salinity could only be due to the process of upwelling. As already mentioned in these works (e.g. by Wyrtki, 1961) during the southeast monsoon, the west-going surface currents coming from the Northern Makassar Strait and the Flores Sea pass the area, and flow into the Java Sea. It is thought that part of the water masses transported by the currents originate from subsurface layer off Makassar coast.